TIMELESS CHARM SEBAGAI UPAYA BRANDING PARIWISATA VIETNAM PERIODE 2012 - 2019 - pujalaksana, ida bagus agung surya; Sushanti, Sukma; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
Vietnam is one of the countries with great potential in the tourism sector. Vietnam issued a Welcome to Vietnam tourism campaign in 2004–2005 and continued with Vietnam the Hidden Charm in 2006-2011. The campaign was quite successful in boosting the prestige of Vietnam's tourism in the eyes of the world, but, of course, there are still some things that must be improved by the government in order to make Vietnam's tourism a quality tourism destination. Therefore, in 2012–2019, Vietnam issued a Timeless Charm campaign as an effort to brand their tourism. To realize this brand, Vietnam made efforts which will be analyzed using the concepts of destination branding and public diplomacy. By using the concept of destination branding and public diplomacy, we get results, namely the various efforts that have been made by the government through their campaigns that directly target the community in the form of infrastructure improvements, natural and human resource management, and improvements to applicable regulations that are implemented quite well. In line with this, Vietnam experienced an increase in tourist arrivals in the 2012-2019 period, which was accompanied by an increase in its FDI. This study used a descriptive qualitative method .